2021
DOI: 10.3390/ijms22169050
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis and Therapeutic Approaches of Diabetic Neuropathy in the Retina

Abstract: Diabetic retinopathy is a major retinal disease and a leading cause of blindness in the world. Diabetic retinopathy is a neurovascular disease that is associated with disturbances of the interdependent relationship of cells composed of the neurovascular units, i.e., neurons, glial cells, and vascular cells. An impairment of these neurovascular units causes both neuronal and vascular abnormalities in diabetic retinopathy. More specifically, neuronal abnormalities including neuronal cell death and axon degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 135 publications
0
23
0
Order By: Relevance
“…Although the exact pathogenesis of RGC loss in DR is still unclear, recent studies have already found a number of clues mediating this process, reviewed by Potilinski et al and Soni et al [ 16 , 17 ]. In brief, RGC apoptosis occurs in the early stage of DR, induced primarily by oxidative stress, extracellular glutamate accumulation and expression alterations of cytokines and neurotrophic factors ( Figure 1 ) [ 19 ]. In addition, ATP-gated cation channels, such as the P2X7 receptor (P2X7R), may also be the targets for RGC death after early-phase injury [ 23 ].…”
Section: Rgc Degeneration In Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact pathogenesis of RGC loss in DR is still unclear, recent studies have already found a number of clues mediating this process, reviewed by Potilinski et al and Soni et al [ 16 , 17 ]. In brief, RGC apoptosis occurs in the early stage of DR, induced primarily by oxidative stress, extracellular glutamate accumulation and expression alterations of cytokines and neurotrophic factors ( Figure 1 ) [ 19 ]. In addition, ATP-gated cation channels, such as the P2X7 receptor (P2X7R), may also be the targets for RGC death after early-phase injury [ 23 ].…”
Section: Rgc Degeneration In Drmentioning
confidence: 99%
“…As a part of the central nervous system (CNS), adult mammalian RGCs cannot proliferate or regrow, and their axons have little capacity to regenerate following damage, which in clinics leads patients to irreversible vision loss. In the past few decades, tremendous study progress has been made in elucidating mechanisms mediating RGC survival using animal models of DM [ 16 , 17 , 18 , 19 ] and in finding regulators of axon regeneration in models of optic nerve injury [ 20 , 21 , 22 ]. In this review, we discuss potential factors modulating optic nerve regeneration strategies in DR by drawing references from studies using optic nerve injury models.…”
Section: Introductionmentioning
confidence: 99%
“…The NVUs are composed of neurons (ganglion cells, amacrine cells, bipolar cells, and horizontal cells), glial cells (Müller cells, astrocytes, and microglia) and vascular cells (endothelial cells and pericytes) [ 19 , 20 , 21 ]. The anatomical and functional interdependence of these cells help to maintain retinal homeostasis and function under healthy conditions.…”
Section: Physiology and Pathology Of Nvu In Diabetic Retinopathymentioning
confidence: 99%
“…In fact, most studies suggest that neuronal changes precede the vascular changes in the clinical findings of the retinas of diabetic patients [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Because neuronal cell death is irreversible and directly related to vision loss, neuroprotection is required to prevent the development and the progression of diabetic neuropathy in the retina at the early stage of diabetic retinas [ 19 , 20 ]. This review focuses on the pathological changes of the NVUs and possible therapeutic options for neuroprotection and vasoprotection of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, blood vessels and nerves are inextricably linked. We should thus not define DR from a single perspective but should consider the interrelationships between multiple factors for a full understanding of the complexity of this disease ( Oshitari, 2021 ).…”
Section: Introductionmentioning
confidence: 99%